Psychomotor and Cognitive Outcome in Very Preterm Infants in Vorarlberg, Austria, 2007–2019 - Jenni, Fabio; Konzett, Karin; Gang, Stefanie; Sparr, Verena; Simma, Burkhard (Neuropediatrics, 2024)
Aim The aim of this study was to analyze neurodevelopmental outcome of very and extremely preterm infants in Vorarlberg, Austria, accessed with neurodevelopmental testing, at the corrected age of 24 months. This article also compared these results with (inter)national data and analyzed the impact of perinatal parameters.Methods Population-based, retrospective multicenter study with data on very and extremely preterm infants born in Vorarlberg from 2007 to 2019 assessed with Bayley Scales of Infant Development (BSID-II/Bayley-III).Results Included were 264 infants with a mean age of 29.0 (± 2.1) weeks of gestational age and a mean birth weight of 1177 (± 328.26) g; 172 infants underwent a BSID-II, 92 a Bayley-III assessment. The psychomotor developmental index (PDI) and mental developmental index (MDI) showed mean scores of 99.6 (± 14.4) and 91 (± 20.4), respectively. Adverse outcomes (scores <70) were assessed in 4.2% for PDI and 15.5% for MDI. In the extremely preterm group (n = 79), results for mean PDI were 100.1 (± 16.8) and for mean MDI 88.4 (± 22.4). Accordingly, adverse outcomes were assessed in 5.1% for PDI and in 20.3% for MDI. In addition to bronchopulmonary dysplasia and intraventricular hemorrhage Grade 3-4, head circumference at birth and patent ductus arteriosus were also identified as risk factors for poor outcome.Conclusion This study showed a remarkably good neurodevelopmental outcome in preterm infants with low rates of adverse outcome, similar to (inter)national reports, especially in the group of extremely preterm infants. Research is needed to explore the role of social factors and infants' environment, especially cognitive outcome and language skills.
Keywords: very preterm infants; neurodevelopmental outcome; Bayley Scales of Infant Development; perinatal risk factors